Echo Boomers’ Job Hopping Behavior: Moderating Role of Emotional Intelligence on Burnout and Career Growth - Nursanti, Tinjung Desy; Salsabila DF, Dhiya (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
The generation of the "echo boomers" or the Millennials is known for their tendency of changing job. They have an intense yearning for professional development and advancement. The features of the previous generation are not the same as the traits of the echo-boomers. They are quick to jump ship if workplace stress begins to negatively impact their mental health and they see opportunities elsewhere to advance their careers. However, it is understood that a person with even average emotional intelligence may plan out each and every one of their major choices. The researchers wanted to know if and how burnout and professional progress influenced job-hopping in the age of remote labor, which is mediated by emotional intelligence. The data was gathered through a survey administered to 142 echo-boomers at DKI Jakarta. Analyses using the MRA (Modified Regression Analysis) tool found that both burnout and career development positively and significantly impacted job hopping. While career development can mitigate the impact of job hopping on emotional intelligence, emotional intelligence cannot moderate the impact of burnout on job hopping.